Kajian Potensi Dan Resiko Keberadaaan Mata Uang Kripto Terhadap Perilaku Investor di Indonesia - Endra Saputra; Jhonson Efendi Hutagalung; Dwi Kurnia Utami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of financial technology is currently so rapid, so that the process of financial transactions carried out by individual users or groups becomes faster. In a period of 10 years, namely 2010-2020, investment is always synonymous with stocks and the capital market. So that investment is always associated with a person or group of people who have a large amount of wealth. Digital currency began to be widely used as a means of payment on the internet. The purpose of this currency is to provide convenience and security in payments. With the Blockchain technology in it, making transaction costs cheaper. In terms of the technology offered, cryptocurrency is a development of financial technology that allows it to replace paper money into digital money in future financial transactions. The behavior of investors in the capital market who generally make investment decisions varies from one investor to another, although sometimes the type of investment chosen is identical and has the same source of information. The purpose of this research is to analyze the potential and risks of the existence of crypto currencies on the behavior of investors in Indonesia. The method used in this study is a descriptive qualitative approach with data collection techniques through literature studies. The results of this study are expected to provide literacy and an explanation of the existence of cryptocurrencies that have potential and risks to investor behavior in Indonesia.